2014
DOI: 10.7861/clinmedicine.14-2-113
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of doctors with the role of physician associates

Abstract: Physician associates (PAs) are a new profession to the UK. There has been no prior national assessment of the perspectives of doctors who work with PAs with regard to their role. Doctors who supervise PAs were surveyed in late 2012; respondents were found generally to be satisfi ed with the role of PAs and believed that the addition of the PA to the team benefi ted doctors and patients. Doctors reported that they have received positive feedback from patients about the role of PAs as well. Respondents believe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 4 publications
3
31
0
Order By: Relevance
“…The issues of regulation and prescribing are also universally reported in empirical reports 11,12 and commentary. 3,13 In the USA, we also see that the most commonly reported reason for employing advanced practice providers (nurse practitioners and physician assistants) was to substitute for residents in the face of medical staffing shortages.…”
Section: Findings In the Context Of Other Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The issues of regulation and prescribing are also universally reported in empirical reports 11,12 and commentary. 3,13 In the USA, we also see that the most commonly reported reason for employing advanced practice providers (nurse practitioners and physician assistants) was to substitute for residents in the face of medical staffing shortages.…”
Section: Findings In the Context Of Other Literaturementioning
confidence: 99%
“…11 Crossing both primary and secondary care, doctors who work with physician associates on a regular basis are reported to be pleased with the role, again limited by regulatory issues. 12 In the UK secondary care setting, the case for the employment of physician associates is made on the stability they might offer to medical teams and their broad medical knowledge in the face of hyperspecialisation. 13 However, we have found no published empirical evidence of the opinions of senior medical staff on employing physician associates in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that the unresolved legal status of PAs is causing uncertainty among doctors about whether or not they are allowed to delegate these more invasive tasks to PAs. 4 If the regulatory issues are resolved and PAs continue to gain experience in emergency care, evidence from the USA suggests that PAs will be able to increase their contribution to the emergency medical team. 5 The NHS desperately needs to evaluate new methods for delivering emergency care.…”
Section: A New Kid On the Block: The Role Of Physician Associatesmentioning
confidence: 99%
“…9 It defines a PA as: Recent studies have reported high levels of patient satisfaction with PAs and other studies examining the attitudes of other healthcare professionals to PA team members have been positive. 10,11 Mean pay for all PAs who work more than 30 hours per week is £35 620 per annum.…”
Section: Physician Assistants/associatesmentioning
confidence: 99%